Interest Rate Ceilings and Financial Exclusion in Kenya: Evidence from Commercial Banks’ Sectoral Credit Distribution - Koskei, Loice (International Journal of Business, Economics and Management, 2020)
The Finance Act that was amended in November 2019 in Kenya saw the removal of the caps on interest charged on loans. The motive of repeal of interest rate caps was to encourage the commercial banks to offer credit to Micro, Small and Medium Enterprises (MSMEs) and other sectors of the economy. The interest rate caps that were implemented in September 2016 led to a significant reduction in lending to the private sector and in particular the small and medium size enterprises and the rural poor which were financially excluded by commercial banks. The main objective of the study was to find out whether interest rate caps contributed to financial exclusion in Kenya’s commercial banks’ sectoral credit portfolio. The target population of the study was 11 private sectors that benefit from commercial banks credit in Kenya. Secondary balanced panel monthly data spanning from January 2016 to December 2019 was used in the study. Fixed effects panel data regression model was used to analyze the data. The results from the study showed a positive and statistically significant relationship between interest rate ceiling and financial exclusion implying that interest rate ceilings affects credit access leading to financial exclusion in Kenya. The results for inflation rate indicated a negative but statistically significant relationship between inflation and financial exclusion implying that inflation affects loan credit growth. The results for exchange rate and public debt are statistically insignificant, suggesting that they do not have an effect on credit access in Kenya’s commercial banks.